The Effect of Management Commitment and Team Orientation on Compliance in Filling Electronic Medical Records with Competence as an Intervening Variable in the Inpatient Installation of Hermina Hospital, Depok - Muhammad Arif Rahman; Rina Anindita; Anastina Tahjoo (Inovasi Kesehatan Global, 2025)
Background: Incomplete electronic medical record filling by doctors can hinder effective action or treatment by other health workers. This non-compliance problem includes incomplete filling and writing of less specific diagnoses, which can potentially lead to errors in nursing action planning. Purposes: This study aims to test the influence of management commitment and team orientation on compliance in filling electronic medical records with competence as an intervening variable in the inpatient installation of Hermina Hospital, Depok. Methods: This research method is quantitative with a cross-sectional study design. The population is doctors at Hermina Hospital Depok who work in the inpatient installation totaling 133 people. The results of the sample calculation obtained 100 respondents. The data collection technique used a questionnaire, and the analysis method used SEM-PLS. Result: The results of the study showed that management commitment, team orientation, and doctor competence had a simultaneous effect on compliance in filling electronic medical records at Hermina Hospital, Depok. Management commitment and team orientation had a significant effect on doctor competence, which in turn also had a direct effect on compliance in filling out medical records. In addition, doctor competence mediated the relationship between management commitment and team orientation on compliance. Improving doctor competence is the main key to ensuring compliance. Conclusion: The conclusion of this study confirms that to improve compliance in filling electronic medical records at Hermina Hospital, Depok, attention is needed to management commitment and team orientation. Improving doctor competence is the main key in ensuring compliance, with competence functioning as a mediator between management commitment and team orientation towards compliance.